The emergence of socioeconomic inequalities in smoking during adolescence and early adulthood - Alves, J (2023)
Background While it is known that educational inequalities in smoking start during early and middle adolescence, it is unknown how they further develop until adulthood. The aim of this article is to map, in the Portuguese context, how educational inequalities in smoking emerge from pre-adolescence until young adulthood. Methods This study used longitudinal data from the EPITeen Cohort, which recruited adolescents enrolled in schools in Porto, Portugal. We included the 1,038 participants followed at ages 13 (2003/2004), 17, 21, and 24 years. We computed the odds ratio (OR) for the prevalence of smoking states (never smoking, experimenter, less-than-daily, daily and former smoker) and the incidence of transitions between these states, as function of age and education, stratified by sex. We also added interaction terms between age and education. Results Educational inequalities in daily smoking prevalence, with higher prevalence among those with lower educational level, emerged at 17 years old and persisted until higher ages. They were formed in a cumulative way by the increased risk of experimenting between 13 and 17 years, and increased risk of becoming daily smoker between 17 and 21 years. The incidence of smoking cessation was higher among the higher educated. Inequalities were formed similarly for women and men, but with lower level and showed no significance among women. Conclusions These results highlight that actions to prevent smoking should also take in account the potential impact in smoking inequalities, and should focus not only on middle adolescence but also on late adolescence and early adulthood.